Identifying risk factors amongst pupils of Groendal Secondary School that make them vulnerable to HIV/AIDS - Adams, Ralphton Antony (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.